Prodomain removal enables neto to stabilize glutamate receptors at the Drosophila neuromuscular junction. - Young-Jun Kim; Oghomwen Igiesuorobo; Cathy I Ramos; Hong Bao; Bing Zhang; Mihaela Serpe (PLoS Genetics)
Stabilization of neurotransmitter receptors at postsynaptic specializations is a key step in the assembly of functional synapses. Drosophila Neto (Neuropillin and Tolloid-like protein) is an essential auxiliary subunit of ionotropic glutamate receptor (iGluR) complexes required for the iGluRs clustering at the neuromuscular junction (NMJ). Here we show that optimal levels of Neto are crucial for stabilization of iGluRs at synaptic sites and proper NMJ development. Genetic manipulations of Neto levels shifted iGluRs distribution to extrajunctional locations. Perturbations in Neto levels also produced small NMJs with reduced synaptic transmission, but only Neto-depleted NMJs showed diminished postsynaptic components. Drosophila Neto contains an inhibitory prodomain that is processed by Furin1-mediated limited proteolysis. neto null mutants rescued with a Neto variant that cannot be processed have severely impaired NMJs and reduced iGluRs synaptic clusters. Unprocessed Neto retains the ability to engage iGluRs in vivo and to form complexes with normal synaptic transmission. However, Neto prodomain must be removed to enable iGluRs synaptic stabilization and proper postsynaptic differentiation.